A Tide of Merit - Tournier, Vincent (Indo-Iranian journal, 2018)
Stressing the importance of 5th–6th-century copper-plate charters connected to the Viṣṇukuṇḍin dynasty for the history of Buddhism in Āndhradeśa, this article demonstrates that, contrary to earlier scholarly assumptions, and despite the paucity of archeological evidence for Buddhist activity at that time, Buddhist lineages still benefitted from lavish donations by ruling families. This study consists of three parts: the first explores the representation of two Viṣṇukuṇḍin rulers as Buddhist kings, and shows how their portraits and their aspirations are permeated by the ideology of the Bodhisattvayāna. The second part examines one of the main recipients of royal donations, the Sthā̆vira/Theriya lineage of the Tāmraparṇīyas, already known from inscriptions issued under the previous Ikṣvāku dynasty. The analysis of these earlier records from Nagarjunakonda in light of little-studied copper plates shows that the Tāmraparṇīyas had a strong institutional presence in Āndhradeśa from the mid-3rd to the late 6th century. The lineage’s connections with Laṅkā and with other Theriya centres along the Bay of Bengal are delineated through a close examination of the terminology used in the inscriptions under scrutiny, in light of co-eval records, and especially of Pāli Vinaya literature and historical narratives. The last part of this article focuses on a poetic allusion to the episode of the Buddha’s victory over Māra included in the opening stanza of a grant issued by king Pr̥thivīśrīmūla. The evidence suggests that this record connects for the first time the water poured by Śākyamuni in his previous lives as a Bodhisattva with a flood that drove away Māra’s army from the seat of Awakening, a motif that grew—like a tide—and spread across Southeast Asia.